Pengaruh Penambahan Fly Ash Terhadap Sifat Workability Dan Sifat Fisik - Mekanik Beton Non Pasir Dengan Agregat Alwa Asal Cilacap - Trisnoyuwono, Diarto (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2015)
A massive concrete production impact on improving air pollution from cement plants. In addition, there are areas has limited aggregate resources that meet building requirement. Building materials technology bring solution for such problems, for example fly ash which can improve the performance of concrete, artificial lightweight aggregate (ALWA) from shale combustion and no-fines concrete. The study aims to determine effect of the fly ash in the mixes of no-fines concrete with ALWA aggregate to the degree of workability and physical - mechanical properties. This research was conducted by the addition of the variable portion of fly ash by 10-20% in comparison mixture of cement - aggregate 1: 4; 1: 6; 1: 8, and the measured value of the slump (workability values) and compressive strength. The results indicate the addition of fly ash were able to increases the value of the slump of up to 7 cm and reach 19.71 MPa of compressive strength.Â